A rare homozygous variant of CHKB induced severe cardiomyopathy and a cardiac conduction disorder: a case report - Jing, Siyuan; Liu, Lu; Li, Yifei; Liu, Fuqiang; Hua, Yimin; Duan, Hongyu (Frontiers in Cardiovascular Medicine, 2024)
Background The CHKB (choline kinase beta) gene plays a crucial role in regulating mitochondrial function and choline metabolism. Mutations in CHKB lead to conditions such as megaconial congenital muscular dystrophy (MCMD), characterized by enlarged mitochondria and impaired mitochondrial function, inducing various clinical features in neurological and cardiac performance. Herein, we report a rare case presenting with dilated cardiomyopathy as the dominant feature with a homozygous nonsense variant of CHKB, and the related therapeutic strategy. Case presentation The proband, a 13-year-old male, presented with a complex clinical profile characterized by mild intellectual disability and severe cardiac impairment, including reduced activity tolerance, suspected acute heart failure, significant cardiac enlargement, a left anterior fascicular block, and a complete right bundle branch block. Whole exome sequencing (WES) identified a homozygous nonsense variant, c.598delC (p.Q200Rfs*11) of the CHKB gene, that resulted in disease caused by amino acid sequence changes, a truncated protein, and splice site changes, as demonstrated by MutationTaster analysis. The protein structure of CHKB was built and named AF-Q9Y259-F1. The residue around 200 amino acid sites changed in CHKB p.Q200Rfs*11 with unaltered hydrogen bonds which indicated the pathogenicity of the variant mainly originated from a truncated protein induced by the nonsense mutation. The heart blocks in the proband were considered to be associated with choline metabolic impairment, and thus cardiac resynchronization therapy would benefit the patient. Furthermore, the missense homozygous or compound heterozygous variants of CHKB, as well as the combined compound heterozygous missense and nonsense variants of CHKB, usually lead to neurological impairments and muscular weakness. Conclusion This study expands the spectrum of CHKB mutations and provides essential information for the genotype–phenotype map of a nonsense variant of the gene. It is important to confirm a differential diagnosis among such patients using WES analyses. Regular cardiac and musculoskeletal monitoring is recommended for MCMD patients. Patients with a CHKB deficiency presenting with heart blocks could benefit from the administration of cardiac resynchronization therapy. This therapeutic approach might improve cardiac function and conduction in patients with CHKB-related cardiomyopathies.